Effect of Core Stability Training on Fine Motor Function in Children with Spastic Cerebral Palsy - Li REN; Shuqin LI (康复学报)
Objective:To explore the clinical significance of core stability training in improving the fine motor function of children with spastic cerebral palsy. Methods: A total of 106 children with spastic cerebral palsy were randomly divided into observation group and control group according to visiting time with 53 cases in each group. The control group received routine rehabilitation training, while the observation group was given core stability training for 12 weeks on the basis of the control group. The gross motor function, general motor function and fine motor function in both groups were assessed by Peabody motor development scale before treatment and 12 weeks after treatment.Results:After treatment, scores of gross motor quotient (GMQ) and total motor quotient (TMQ) in both groups were higher than those before treatment (P<0.05). The difference of GMQ scores and TMQ scores in the observation group were higher than those in the control group (P<0.05). Standard scores for grasp, visual-motor integration and fine motor quotient (FMQ) scores in both groups were higher than those before treatment (P<0.05). The difference of standard scores for grasp, visual-motor integration and FMQ scores in the observation group were higher than those in the control group (P<0.05).Conclusion:Core stability training can effectively improve the core stability of children with spastic cerebral palsy and promote the development of their fine motor function.